2004
DOI: 10.1152/ajpcell.00387.2003
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of STAT3 in human monocytes stimulated by G-CSF: implication in inhibition of LPS-induced TNF-α production

Abstract: Lipopolysaccharide (LPS) induced tumor necrosis factor (TNF)-α production in human monocytes, which was dependent on activation of extracellular signal-regulated kinase (ERK), p38, c-Jun NH2-terminal kinase (JNK), and nuclear factor (NF)-κB. LPS-induced TNF-α production was inhibited by granulocyte colony-stimulating factor (G-CSF) and interleukin (IL)-10. G-CSF, like IL-10, exerted the inhibitory effect even when simultaneously added with LPS. Among the signaling pathways, signal transducer and activator of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 60 publications
2
46
0
2
Order By: Relevance
“…54 While the mechanism governing G-CSF-mediated cytokine inhibition remains unclear, recent studies have suggested a role for STAT3. 58,59 Collectively, these data suggest an important role for G-CSF in the down-regulation of the local inflammatory response.…”
Section: Discussionmentioning
confidence: 83%
“…54 While the mechanism governing G-CSF-mediated cytokine inhibition remains unclear, recent studies have suggested a role for STAT3. 58,59 Collectively, these data suggest an important role for G-CSF in the down-regulation of the local inflammatory response.…”
Section: Discussionmentioning
confidence: 83%
“…Accumulated evidence suggests that mitochondria play a critical role in macrophage-mediated innate immunity, and mitochondrial ROS generation is implicated in cytokine production and bactericidal activity in macrophages [43,44,45,46]. Our previous study shows that mitochondrial density and/or the respiratory state affect the level of mitochondrial ROS generation, which is closely associated with MAPK activation and cytokine production in macrophages stimulated with LPS [13,47]. …”
Section: Discussionmentioning
confidence: 97%
“…These cascades include JAK2 -STAT3, PI3 Kinase -AKT, and ERK 1/2 (Nishiki et al, 2004, Schabitz et al, 2003, Schneider et al, 2005, Solaroglu et al, 2003. Recent work suggests that these intracellular cascades are upregulated selectively in different brain regions, and in different cell types within the brain.…”
Section: Introductionmentioning
confidence: 99%